Copper improves the anti-angiogenic activity of disulfiram through the EGFR/Src/VEGF pathway in gliomas. Issue 1 (1st December 2015) - Li, Yi; Fu, Shi-Yuan; Wang, Li-Hui; Wang, Fang-Yang; Wang, Nan-Nan; Cao, Qi; Wang, Ya-Ting; Yang, Jing-Yu; Wu, Chun-Fu
Highlights: DSF potently inhibited angiogenesis both in vitro and in vivo . Cu improves the anti-angiogenic ability of DSF both in vitro and in vivo . DSF/Cu suppresses VEGF secretion through EGFR/c-Src/VEGF pathway. Abstract: Disulfiram (DSF) possesses anticancer activity by inducing apoptosis in vitro and in vivo in a copper (Cu)-dependent manner. DSF also potently inhibits angiogenesis, but the effect of Cu on this anti-angiogenic activity is unknown. Here we show that DSF inhibits the proliferation, migration, invasion, adhesion and complex tube formation of human umbilical vascular endothelial cells (HUVECs). Aortic ring assays and Matrigel plug assays revealed that DSF significantly inhibited the formation of microvessels. Importantly, Cu improved the anti-angiogenic activity of DSF in all these assays, while copper alone had no effect. DSF/Cu treatment of U87 human glioblastoma cells resulted in suppression of VEGF secretion through the EGFR/c-Src/VEGF pathway. Reduction of EGFR phosphorylation disables recruitment of multiple Src homology 2 (SH2) domains, resulting in transcriptional down-regulation of VEGF. The role of EGFR/c-Src/VEGF pathway was further confirmed by using specific inhibitor, which significantly improved the anti-angiogenic activity of DSF/Cu. DSF/Cu also exerted increased anti-tumor effects on subcutaneous and intracerebral U87 xenograft models by reducing microvessel density (MVD) and VEGF expression. These results indicate that Cu improves the anti-angiogenic activity of DSF by targeting the EGFR/Src/VEGF signaling pathway, thus providing a rationale for the use of DSF/Cu rather than DSF alone as an angiogenesis inhibitor in clinical applications.